Farm Animal-Assisted Therapy for Individuals with Autism Spectrum Disorder: Parent’s Perspectives - Dolecheck, Mackenzie P (East Carolina University, 2023)
Autism Spectrum Disorder (ASD) is a developmental disorder that affects an individual's ability to communicate, create social relationships, and regulate sensory input and repetitive behaviors. An uncommon intervention used in ASD treatment is farm animal assisted therapy (AAT). AAT interventions focus on the use of animals in adjunct to achieve goals and outcomes. Farm AAT is defined as the use of farm animals such as cows, sheep, goats, horses, and pigs in AAT interventions. There is a lack of evidence on the use of farm animals and their benefits within the scope of AAT and in recreational therapy. The purpose of this study was to provide evidence, from the perspective of parents, of the potential benefits of farm AAT as a recreational therapy intervention for individuals with ASD. Data collection using a semi-structured interview guide was conducted over the phone with parents who participated in family session programs at the study location. Five participants were selected who matched the inclusion criteria for this study. The findings from this study reported that there were increases in social behaviors, regulation of behaviors, and a sense of normalcy for the children. The findings from this study will provide a foundation for future research related to farm AAT such as evidenced-based curriculums and practices. The data will provide therapists and parents with an understanding of the potential benefits that are gained from participation in farm AAT interventions.
Keywords: farm animal-assisted therapy; animal-assisted therapy; social behaviors, behavioral regulation; sense of normalcy; Livestock--Therapeutic use; Autistic children--Behavior modification; Parents of autistic children--Attitudes; Recreational therapy for children; Human-animal relationships